Towards an evaluation of the nexus between unfettered, unregulated capitalism, donor aid and debt relief inconsistencies, and the problem of post-election violence in Kenya. Issue 1 (2nd January 2023) - Omulo, Albert Gordon
ABSTRACT: Although internal structural factors in emerging democracies and factors related to the electoral process and contest remain indispensable in understanding post-election violence, they are not sufficient in an era of full-fledged neoliberal globalisation, enshrined in the Washington Consensus and the productivist development model enforced by the World Bank. Accordingly, this paper approaches electoral violence in Africa through the lens of unfettered, unregulated capitalism. Based on insights from Belgian historian Éric Toussaint, it assumes the posture that violent contestation of state power, in Kenya, is also indicative of the insatiable pursuit of profit, by global capitalists. Grounded in historical data from Human Rights Watch annual reports (1991–2008), it tests, through Kenya's first four multiparty elections conducted during the Moi and Kibaki eras, covering the period 1992–2007, the hypothesis that ' Aid and debt relief inconsistencies by donors and international financial institutions have emboldened the Kenyan government to disregard human rights, leading to impunity, which has yielded post-election violence '. It finds, partly, that 'donors seem willing to countenance harassment and intimidation of the Kenyan government's critics as long as the government continues to liberalize the economy and retain a multiparty system in name', an element that could also explain post-election violence.